ANTIMICROBIAL ACTIVITY OF WATER-ETHANOLIC EXTRACTIONS FROM QUERCUS ROBUR L. LEAVES AND BUDS - N. A. Ryabov; V. M. Ryzhov; V. A. Kurkin; S. D. Kolpakova; A. V. Zhestkov; A. V. Lyamin (Фармация и фармакология (Пятигорск), 2021)
The problem of finding new antimicrobial drugs based on medicinal plant raw materials in modern pharmaceutical practice, is still relevant. There are interesting plant objects that have an antimicrobial action due to the content of a complex of biologically active substances in them. Quercus robur L. is a promising plant object, medicinal plant raw materials of which can be used for the development of new antimicrobial drugs.The aim of the study is screening of the antimicrobial activity of water-ethanolic extractions from Quercus robur L leaves and buds.Materials and methods. The determination of the minimum inhibitory concentration was carried out by the method of double serial dilutions in Mueller-Hinton nutrient broth (Bio-Rad, USA). As test cultures, strains of microorganisms of the American Type Culture Collection (ATCC) were used: Staphylococcus aureus (ATCC 29213), Escherichia coli (ATCC 25922), Pseudomonas aeruginosa (ATCC 27853), as well as Candida albicans (a clinical strain). The incubation was carried out at the temperature of 35°C for 24 hours. Simultaneously, an experiment was carried out to establish a "negative" control. The results were assessed visually by the presence / absence of the growth of microorganisms in test tubes with the corresponding dilutions of the test samples.Results. In the course of the study, it was found out that water-ethanolic extractions of Quercus robur L. leaves have the greatest antimicrobial effect against strains of Staphylococcus aureus and Escherichia coli. The water-ethanolic extractions of Quercus robur L. buds exhibit a pronounced antimicrobial activity against Pseudomonas aeruginosa and Candida albicans strains.It was revealed that the preparation of Quercus robur L. leaves tincture in the raw material:extractant ratio of 1:5 has a pronounced antimicrobial effect on the strains of Pseudomonas aeruginosa, Staphylococcus aureus, and with a higher multiplicity of dilution - on the strains of Escherichia coli and Candida albicans. The drug tincture of Quercus robur L. buds in the raw material:extractant ratio of 1:5 has a pronounced antimicrobial effect on the strains of microorganisms P. aeruginosa, S. aureus, E. coli and C. albicans in an eight-fold dilution. With respect to P. aeruginosa strains, antimicrobial activity was observed in 16-fold dilutions. The most pronounced antimicrobial effect was recorded against the C. albicans strain in a 32-fold dilution.As a result of the study, it can be concluded that to obtain the antimicrobial drugs - tincture of Quercus robur L. leaves and buds - is advisable to use the optimal extractant – 70% alcohol in a raw material:extractant ratio of 1:5. With these parameters of extraction, the greatest antimicrobial effect is observed in relation to the studied strains of the microorganisms. 70% alcohol has also a better penetrating ability into the deep layers of the epidermis in comparison with higher concentrations.Conclusion. The results of the screening analysis of the antimicrobial activity will be used as a justification for the introduction of antimicrobial drugs based on the leaves and buds of the Quercus robur L. in a medical and pharmaceutical practice.